(untitled) (Scientific journal of the Fergana State University, 2025)
This study explores the lexical typology of units expressing «gratitude» in English and Uzbek, aiming to compare and contrast the ways in which both languages encode and express the concept of gratitude. The research analyzes a range of expressions, including single words, phrases, and fixed formulas used to convey appreciation, thankfulness, or indebtedness in social interactions. The study first examines the key expressions of gratitude in both languages, such as the English phrases «thank you,» «thanks,» and «I appreciate it,» alongside the Uzbek equivalents like «rahmat,» «minnatdorman,» and other culturally specific forms. The focus is on the structural and semantic aspects of these expressions, with attention to variations in formality, politeness, and context. The research also delves into the cognitive and cultural frameworks that shape the way gratitude is conceptualized and verbalized in these two languages. For instance, English tends to use more direct, individualistic expressions of thanks, while Uzbek may include more elaborate and honorific forms of gratitude, influenced by social hierarchies and communal values. Additionally, the study addresses the syntactic and pragmatic variations between these two languages, analyzing the use of gratitude in different communicative settings, such as casual conversations, formal speeches, and written expressions. Special attention is given to the non-verbal cues and gestures that often accompany expressions of gratitude in both languages, as these contribute to the overall communicative intention. By identifying the similarities and differences in how gratitude is lexicalized in English and Uzbek, the study provides insights into the cultural and linguistic mechanisms of expressing appreciation, contributing to a deeper understanding of cross-cultural communication and language typology.